2007
DOI: 10.1007/978-3-540-74974-5_4
|View full text |Cite
|
Sign up to set email alerts
|

Faster and More Focused Control-Flow Analysis for Business Process Models Through SESE Decomposition

Abstract: We present a technique to enhance control-flow analysis of business process models. The technique considerably speeds up the analysis and improves the diagnostic information that is given to the user to fix control-flow errors. The technique consists of two parts: Firstly, the process model is decomposed into single-entry-single-exit (SESE) fragments, which are usually substantially smaller than the original process. This decomposition is done in linear time. Secondly, each fragment is analyzed in isolation us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
180
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 194 publications
(187 citation statements)
references
References 15 publications
5
180
0
2
Order By: Relevance
“…Applying such techniques to real-life models typically results in the discovery of many errors. This has been demonstrated in some recent case studies [MMN + 06, MVD + 08, FFJ + 09, MNA07,VVL07].…”
Section: Resultssupporting
confidence: 63%
See 1 more Smart Citation
“…Applying such techniques to real-life models typically results in the discovery of many errors. This has been demonstrated in some recent case studies [MMN + 06, MVD + 08, FFJ + 09, MNA07,VVL07].…”
Section: Resultssupporting
confidence: 63%
“…This more refined analysis showed that 20.9 percent of the SAP models are actually flawed. In [VVL07] a set of 340 real business processes modeled with the IBM WebSphere Business Modeler is analyzed. We would also like to point to the comparative analysis of various workflow verification approaches described in [FFJ + 09].…”
Section: Related Workmentioning
confidence: 99%
“…Metrics including size, complexity and coupling are validated for their correlation with understanding and maintainability [31,32]. Further metrics aim to quantify cognitive complexity and modularity [33,34,35,36]. Various metrics have been validated as predictors of error probability [37], which is assumed to be a symptom of bad understanding by the modeler during the process of model creation.…”
Section: Structural Factors Of Process Model Understandingmentioning
confidence: 99%
“…Hence, the observed behavioral constraint coincides with the behavioral constraint imposed by the model. A prominent example of activity groups that fulfill the defined requirement are groups resulting from the canonical decomposition of a process model into single entry single exit fragments, see [18,19].…”
Section: Definition 8 (Behavioral Inconsistency) Letmentioning
confidence: 99%